2019
DOI: 10.1002/ange.201908279
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Synthesizing Axially Chiral Naphthyl‐Indoles: Catalytic Asymmetric Addition Reactions of Racemic Substrates

Abstract: An ew strategy for enantioselective synthesis of axially chiral naphthyl-indoles has been established through catalytic asymmetric addition reactions of racemic naphthylindoles with bulky electrophiles.Under chiral phosphoric acid catalysis,a zodicarboxylates and o-hydroxybenzyl alcohols served as bulky but reactive electrophiles that were attacked by C2-unsubstituted naphthyl-indoles,w hich underwent ad ynamic kinetic resolution to affordt wo series of axially chiral naphthyl-indoles in good yields (up to 98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 160 publications
0
11
0
Order By: Relevance
“…The utilization of the strategy of DKR via asymmetric organocatalysis to accessa xially chiral arylindoles had not been realized until recently.T he Shi group utilized racemic arylindoles 32 as suitables ubstrates for asymmetricn ucleophilic additions with bulky electrophiles such as azodicarboxylates 33 and ohydroxybenzyl alcohols 35 in the presence of CPAs (Scheme 9a). [29] The two reactions successfully underwent a DKR process to give two types of axially chiral arylindoles (34 and 36)i nh igh yields with excellent stereoselectivities.N otably,a rylindoles 36 have both axial and central chirality.T he suggested reaction pathway of this organocatalytic DKR (Scheme9b) indicated that the matched steric configurations between catalyst (S)-C7 and (S a )-32 a led to the conversion of (R a )-32 a into (S a )-32 a and the continuous generation of naphthylindole (R a )-34 a with relatively stable axial chirality.…”
Section: Axially Chiral Arylindolesmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of the strategy of DKR via asymmetric organocatalysis to accessa xially chiral arylindoles had not been realized until recently.T he Shi group utilized racemic arylindoles 32 as suitables ubstrates for asymmetricn ucleophilic additions with bulky electrophiles such as azodicarboxylates 33 and ohydroxybenzyl alcohols 35 in the presence of CPAs (Scheme 9a). [29] The two reactions successfully underwent a DKR process to give two types of axially chiral arylindoles (34 and 36)i nh igh yields with excellent stereoselectivities.N otably,a rylindoles 36 have both axial and central chirality.T he suggested reaction pathway of this organocatalytic DKR (Scheme9b) indicated that the matched steric configurations between catalyst (S)-C7 and (S a )-32 a led to the conversion of (R a )-32 a into (S a )-32 a and the continuous generation of naphthylindole (R a )-34 a with relatively stable axial chirality.…”
Section: Axially Chiral Arylindolesmentioning
confidence: 99%
“…In addition, ap reliminary evaluation on the cytotoxicity of axially chiral naphthylindoles 34 and alkene-indoles 74 to various cancer cell lines revealed that compounds 34 a-34 e and 74 a displayed potent anti-cancer activity (Figure 4), [29,47] which highlighted the future application of axially chiral indole-based scaffoldsi nt he discoveryo fp harmaceutically relevant molecules.…”
Section: Applications Of Axially Chiral Indole-based Scaffoldsmentioning
confidence: 99%
“…Shi reported the strategy for enantioselective synthesis of axially chiral naphthyl‐indoles by means of SPA‐catalyzed asymmetric addition reactions of naphthylindoles with bulky electrophiles (Scheme 52). [ 57 ] O ‐Hydroxybenzyl alcohols were employed as bulky but reactive electrophiles, attacked by C2 ‐unsubstituted naphthyl‐indoles, which underwent adynamic kinetic resolution to afford axially chiral naphthyl‐indoles with high yields (up to 97%) and generally excellent diastereo‐ and enantioselectivities (>95 : 5 d.r. and up to 96% ee).…”
Section: Asymmetric Organocatalysismentioning
confidence: 99%
“…In the same year, Shi and co‐worker developed a dynamic kinetic resolution (DKR) approach for the preparation of axially chiral naphthyl‐indoles by taking advantage of CPA‐catalyzed asymmetric addition of racemic C2‐unsubstituted naphthyl‐indoles 67 with bulky electrophiles, including azodicarboxylates 68 and o ‐hydroxybenzyl alcohols 69 [29] . Under the optimized reaction conditions, two sets of axially chiral naphthyl‐indoles 70 and 71 were synthesized in good yields and stereoselectivities (up to 98 % yield, up to >95 : 5 dr , 96 % ee ).…”
Section: Construction Of Indole‐containing Atropisomersmentioning
confidence: 99%